Dissenting social work : critical theory, resistance and pandemic - Garrett, Paul Michael, 1958- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book, from one of international social work's leading radical educators, provides a richly compelling argument for the profession to become more critical and dissenting. Addressing the troubled times in which we find ourselves, Garrett's book examines a broad range of theoretical frameworks and draws on diverse writers, such as Marx, Foucault, Brown, Zuboff, Rancière, Wacquant, Arendt, Levinas, Fanon and Gramsci. The author's panoramic vision encompasses Ireland, the UK, the US, Algeria, Israel/Palestine and China. Timely, lively and accessible, this book speaks directly to some of the main preoccupations of our era. Readers will be encouraged to relate developments in social work to key themes circulating around migration, the threat of neo-fascism, surveillance culture, colonialism, the Black Lives Matter movement and COVID-19 pandemic. Imbued with a sense of hope for a brighter future, this book encourages a new generation of social work students to recognise and examine the importance of critical theory for understanding the structural forces shaping their lives and the lives of those with whom they work and provide services. This book is vital, indispensable and essential reading for social work students and other readers, throughout the world, seeking to make the connection between social work, social theory and sociology"--
OCLC-licensed vendor bibliographic record.
Keywords: Social service; Social movements; COVID-19 (Disease) -- Social aspects; SOCIAL SCIENCE / Sociology / General